A System for Monitoring Workers' Safety in an Unhealthy Environment by means of Wearable Sensors - Corbellini, S.; Ferraris, F.; Parvis, M. (2008 IEEE Instrumentation and Measurement Technology Conference, 2008)
This paper describes a system for monitoring the safety of workers who are exposed to unhealthy environments. The system is based on a low-cost wireless network of smart wearable buttons that can be applied inside the protective suits and that embed the measurement device along with a 2.4 GHz radio. The proposed solution is conceived to be employed with elements that use textile fibres as intrinsic sensors and with discrete sensors as well. The network allows both the measurement strategy and the program code of the wearable sensors to be remotely updated in order to adapt and optimize the power consumption. The real-time operability is also permitted by introducing proxy elements that allow the network area to be extended in a solution similar to that of the Zigbee but optimized for the required architecture. The system can be employed in a wide class of indoor medical applications; an example is provided that is intended to monitor temperature and humidity for workers inside refrigerated chambers.